2016
DOI: 10.1111/pace.12821
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Female Sex Hormones on Ventricular Premature Beats and Repolarization Parameters in Physiological Menstrual Cycle

Abstract: VPB frequency decreases with estradiol peak in the ovulation period. This suggests that estrogen may have protective effects against ventricular arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…1,6 During the follicular phase, associated with a higher ratio of estrogen to progesterone concentration, the ventricular action potential and QT interval are prolonged in comparison with the luteal phase. These differences may explain some of the changes in arrhythmia frequency that have been reported during the menstrual cycle, including an increased risk for torsade de pointes VT during the follicular phase of the ovarian cycle.…”
Section: Sex Differences In Cardiac Electrophysiologymentioning
confidence: 99%
“…1,6 During the follicular phase, associated with a higher ratio of estrogen to progesterone concentration, the ventricular action potential and QT interval are prolonged in comparison with the luteal phase. These differences may explain some of the changes in arrhythmia frequency that have been reported during the menstrual cycle, including an increased risk for torsade de pointes VT during the follicular phase of the ovarian cycle.…”
Section: Sex Differences In Cardiac Electrophysiologymentioning
confidence: 99%
“…In our study there was no significant change regarding supraphysiological oestradiol levels in terms of QT dispersion and corrected QT dispersion. Also, in the study in which we compared hormonal changes during physiological menstrual cycle and ECG and 24-h Holter ECG findings, there was no correlation between ovulation and QT dispersion [19]. There are also other studies showing that there is no significant relation between menstrual cycle and QT dispersion [4].…”
Section: Discussionmentioning
confidence: 81%
“…It was reported that there were lower levels of estradiol in cases with idiopathic ventricular outflow tract arrhythmia compared to controls, 9 and that there were fewer counts of PVCs in the ovulation period than in the menstruation period. 10 Female sex hormones, especially estrogen, were suggested to play an important role in these clinical results. For premenopausal women, estrogen levels remain high during the ovulation phase and abruptly decrease at the end of the ovulation phase and become low at the beginning of the menstruation phase.…”
Section: Discussionmentioning
confidence: 99%